(untitled) (Journal of Civil Engineering Researchers, 2023)
Lack of proper municipal solid management in the Northern provinces of Iran has led to damages to the natural resources, health, environment, social and economic conditions. Construction of solid waste processing plants such as compost and incineration, ignoring essential elements in waste management, cannot be as a successful strategy to solve the solid waste problems. Integrated management as a suitable and well-proved solution in many developed countries was proposed for Mazandaran province as a more reliable strategy to replace the existing conditions. In this paper, the results of study conducted for Amol and Noor region have been analyzed. Minimizing waste production, maximizing recycling and reuse, processing organic waste through digestion or composting process, producing refusing derived fuel (RDF) and using it in the waste incineration plants or Neka cement plant and finally disposing less than 10% of the waste in landfill is the proposed solution to improve the existing waste conditions. Implementing the proposed integrated management over a period of 20 years will lead to preventing from economic and environmental damages due to the loss of valuable natural resources and the release of various pollutants from landfills which is evaluated to be equivalent of about 28 billion dollars also, saving resources and energy estimated to be about 38 billion dollars.